CURRENT TRENDS IN THE DEVELOPMENT OF THE PRINCIPLES OF INHERITANCE LAW - Stojanovic, Natasa (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
In a legal system each branch of law has its fundamental rules, the guiding ideas upon which the entire construction of legal norms constituting it has been built, and which regulate a number of related types of certain social relations. Inheritance law, as a part of civil law family, does not depart from it and adapts its basic principles to the basic principles of civil law, the requirements of legal tradition, but also the needs of society in a corresponding period of its development. In the Civil Code of the Republic of France, its part dedicated to the institute of successions, in the Civil Code of the Russian Federation, in the part governing succession rights, and in the Law of Inheritance of the Republic of Serbia, the basic rights are distributed in different parts of legal texts, which partially makes it difficult to find and connect them into one legal and logical whole, and consequently to apply them in practice. In this paper, by virtue of legal and dogmatic, normative and legal, comparative and legal, and historical and legal methods, we endeavour to establish − through a prism of legal solutions, theoretic concepts and stands of jurisprudence − the basic principles of contemporary French, Russian and Serbian inheritance law; we analyse them and consider their meaning and reach in the regulation of inheritance and legal relations. Since French, Russian and Serbian inheritance and legal regulations have been amended a number of times so far, with this paper we particularly want to highlight the current trends in the development of basic principles of inheritance law in order to determine a further direction of the development of inheritance and law regulations in these countries.